2013
DOI: 10.3126/ijim.v1i2.7407
|View full text |Cite
|
Sign up to set email alerts
|

Status of tuberculosis in bovine animals raised by tuberculosis infected patients in Western Chitwan, Nepal

Abstract: INTRODUCTION: Bovine tuberculosis (bTB) is an important public health concern worldwide. This study was conducted to determine the status of bTB in animals raised by tuberculosis patients in Western Chitwan, Nepal. MATERIALS AND METHODS: This cross-sectional study was conducted from August, 2011 to January, 2012. A total of 100 bovines (cattle and buffalo) raised in 60 farms of tuberculosis patients were tested with single intradermal tuberculin test considering various animal factors. Well designed questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Raw milk drinking habit exists in Nepalese society and the awareness about zoonotic diseases is very low. 15 The seropositivity found in this study indicates the threat existing in these areas. In such circumstances, there is need of increasing public awareness for changing their behavior and practices together with implementation of regular screening and adoption of better prevention and control strategy, so as to protect animal and human health.…”
Section: Discussionmentioning
confidence: 52%
“…Raw milk drinking habit exists in Nepalese society and the awareness about zoonotic diseases is very low. 15 The seropositivity found in this study indicates the threat existing in these areas. In such circumstances, there is need of increasing public awareness for changing their behavior and practices together with implementation of regular screening and adoption of better prevention and control strategy, so as to protect animal and human health.…”
Section: Discussionmentioning
confidence: 52%
“…bovis strains in Kathmandu and Kaski from limited cattle and buffalos' samples in 2007. A cross-sectional study conducted by Pandey et al [ 26 ] in Chitwan reported the prevalence of bovine TB was up to 15% in 100 cattle sampled. However, due to the lack of a coordinated national surveillance program on bovine TB in human health and animal health services, the exact prevalence of bovine TB is unknown either in human or animal populations.…”
Section: Introductionmentioning
confidence: 99%
“…Since livestock is an indispensable part of Nepal's agricultural system, buffaloes and cattle are often kept close to each other, which increases potential spread of M. bovis. Pandey et al (2013) found that in Chitwan district (southern Terai) bovine TB was found in 15% of cattle and buffaloes. The study was also conducted on cattle and buffaloes that were raised by farmers who were under directly observed treatment (DOT), which indicates that TB may have been acquired from the animals (Pandey et al, 2013).…”
Section: Health Burden Of Zoonoses In Humansmentioning
confidence: 99%
“…In Nepal, the overall prevalence of bovine tuberculosis in buffaloes and cattle has been found to be 9.08% and 5.78%, respectively (Joshi, Heidmann and Sollod, 1999). The prevalence of tuberculosis in buffaloes in Chitwan valley was recently recorded at 15.4% (Pandey et al, 2013). A total of 36 mycobacterial strains isolated from 39% of the buffaloes (14 of 36) and 34% of the cattle (11 of 32) were found positive on the single intradermal cervical tuberculin (SICT) test (Jha et al, 2007).…”
Section: Bovine Tuberculosismentioning
confidence: 99%